2017
DOI: 10.1242/dev.148270
|View full text |Cite
|
Sign up to set email alerts
|

Prostate organogenesis: tissue induction, hormonal regulation and cell type specification

Abstract: Prostate organogenesis is a complex process that is primarily mediated by the presence of androgens and subsequent mesenchyme-epithelial interactions. The investigation of prostate development is partly driven by its potential relevance to prostate cancer, in particular the apparent re-awakening of key developmental programs that occur during tumorigenesis. However, our current knowledge of the mechanisms that drive prostate organogenesis is far from complete. Here, we provide a comprehensive overview of prost… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
129
0
2

Year Published

2019
2019
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 146 publications
(141 citation statements)
references
References 226 publications
2
129
0
2
Order By: Relevance
“…Studies have shown that mediators secreted by macrophage may interact with Leydig cells as well as other cells present in testes, thereby causing the hypoandrogenism related to the arthritis (Clemens & Bruot, ; Bruot & Clemens, ; Bendele et al ., ). In this manner, this slight reduction in the prostate wet mass may be a consequence of an AIA‐induced hypoandrogenism because this gland is an androgen‐dependent organ (Toivanen & Shen, ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Studies have shown that mediators secreted by macrophage may interact with Leydig cells as well as other cells present in testes, thereby causing the hypoandrogenism related to the arthritis (Clemens & Bruot, ; Bruot & Clemens, ; Bendele et al ., ). In this manner, this slight reduction in the prostate wet mass may be a consequence of an AIA‐induced hypoandrogenism because this gland is an androgen‐dependent organ (Toivanen & Shen, ).…”
Section: Discussionmentioning
confidence: 99%
“…Like the testes, the male sex glands can also be affected by RA, as they are androgen‐dependent organs. Actually, testosterone is essential for both the proliferation of the epithelium and the secretory activity of these glands (Toivanen & Shen, ; McKay & Sharma, ). Furthermore, it cannot be ruled out that inflammatory mediators from the injured joints can act directly on the male sex glands, regardless of hypoandrogenism secondary to arthritis.…”
Section: Introductionmentioning
confidence: 99%
“…Mezodermal kökenli olan mezonefrik (Wolffian kanalı) ve paramezonefrik (Müller kanalı) kanalları, genitoüriner sistemin gelişmesinde görev alır. 10 Wolffian kanalının yapıları testosteron kontrolü ile oluşurken, ürogenital sinüs gelişimi DHT bağımlıdır. Tam prostat morfogenezi için, testosteronun 5α redüktaz ile hücre içi DHT'ye dönüştürülmesi gereklidir.…”
Section: Prostat Bezi̇unclassified
“…Its interaction with organ-specific hormone signals may be important for orchestrating the functions of adult stem cells in that tissue. In the prostate, both the canonical Wnt signaling and androgen signaling pathways have been shown to be essential in driving organogenesis (Toivanen and Shen, 2017). Specifically, stromal Wnt secretion promotes prostate bud branching morphogenesis and expression of the prostatespecific transcription factor Nkx3.1 in the epithelium (Francis et al, 2013;Julio et al, 2013;Simons et al, 2012).…”
Section: Introductionmentioning
confidence: 99%